Proposed Quality Performance Indicators (QPI's) for axillary lymphadenectomy in metastatic cutaneous melanoma. Issue 12 (December 2021) - Ollek, Sita; Wen, Daniel; Ong, Ian; Anderson, William; Harman, Richard; Martin, Richard
Abstract: Introduction: Axillary lymph node clearance (ALNC) continues to play a central role in the management of melanoma. However, what defines an adequate lymphadenectomy remains unclear. We aimed to propose Quality Performance Indicators (QPIs) for ALNC and to determine if the number of lymph nodes (LNs) removed impacts survival. Methods: We reviewed patients who underwent ALNC for melanoma at the Waitemata District Health Board and Melanoma Unit between February 2005 and October 2019, performed by two surgeons with standardized technique and surveillance. Results: 105 patients with stage III melanoma were included, of which 73 had clinically evident disease and 32 had clinically occult disease. The mean total number of LNs excised was 29 (SD 10.90, range 10–76). On multivariate analysis, lymph node ratio (HR 4.48, 95% CI 1.55–12.93, p = 0.006), extracapsular spread (HR 2.53, 95% CI 1.06–6.05, p = 0.036) and distant recurrence (HR 11.24, 95% CI 3.79–33.31, p < 0.001) were significant predictors of mortality. The number of LNs removed did not predict survival outcomes, while the lymph node ratio did significantly predict survival outcomes. The regional recurrence rate was 3.8%. Discussion: We propose that QPIs for ALNC in melanoma include a 90th percentile LN yield of greater than 15, a mean LN yield of 20, a regional recurrence rate of less than 10%, and an overall complication rate of less than 50%. Conclusion: The establishment of QPIs can help ensure that surgical oncology patients receive the highest quality of care.